Professional Values and Managerialist Practices: Values work by nurses in the emergency department. Issue 9 (September 2021) - Wright, April L.; Irving, Gemma; Selvan Thevatas, Kalai
Interest in values work – the purposeful effort of actors to create, maintain and disrupt the values of organizations, professions and other institutions – is growing among scholars. We ask: How do frontline professionals engage in values work while enacting managerialist practices inside organizations? We investigate this question using a case study of nurses enacting managerialist practices associated with time-efficient work flow in a hospital emergency department in Australia. Our findings show that professionals engage in values work by categorizing the values of the profession and taking actions within the managerialist practice to (1) defend a superordinate value category, (2) contain erosion of a subordinate value category, and (3) integrate a basic value category. Our study brings attention to how multiple values complicate the processes of values work when particular values become implicated in organizational practices. Frontline professionals become motivated and take actions to accomplish values within a relational system of multiple values according to relative importance and relevance to the local context. Our study offers a way forward for understanding the performance of values work within the 'new normal' for professions in contemporary organizational contexts.